GATA6 Mutations Cause a Broad Phenotypic Spectrum of Diabetes From Pancreatic Agenesis to Adult-Onset Diabetes Without Exocrine Insufficiency - De Franco, Elisa (American Diabetes Association, 2013)
We recently reported de novo GATA6 mutations as the most common cause of pancreatic agenesis, accounting for 15 of 27 (56%) patients with insulin-treated neonatal diabetes and exocrine pancreatic insufficiency requiring enzyme replacement therapy. We investigated the role of GATA6 mutations in 171 subjects with neonatal diabetes of unknown genetic etiology from a cohort of 795 patients with neonatal diabetes. Mutations in known genes had been confirmed in 624 patients (including 15 GATA6 mutations). Sequencing of the remaining 171 patients identified nine new case subjects (24 of 795, 3%). Pancreatic agenesis was present in 21 case subjects (six new); two patients had permanent neonatal diabetes with no enzyme supplementation and one had transient neonatal diabetes. Four parents with heterozygous GATA6 mutations were diagnosed with diabetes outside the neonatal period (12–46 years). Subclinical exocrine insufficiency was demonstrated by low fecal elastase in three of four diabetic patients who did not receive enzyme supplementation. One parent with a mosaic mutation was not diabetic but had a heart malformation. Extrapancreatic features were observed in all 24 probands and three parents, with congenital heart defects most frequent (83%). Heterozygous GATA6 mutations cause a wide spectrum of diabetes manifestations, ranging from pancreatic agenesis to adult-onset diabetes with subclinical or no exocrine insufficiency.